Winning at the acquisition game tools, templates, and best practices across the m&a process - Galpin, Timothy (Gildan Audio, 2020)
In an era of digital transformation, disruptive innovation, transient competitive advantage, and industry convergence, mergers and acquisitions have become more complex than ever.Winning at the Acquisition Game presents the best materials, insights, and tools which comprise the comprehensive, cross-disciplinary Mergers and Acquisitions course taught in the MBA and Executive MBA programs at the SaId Business School, University of Oxford. Each chapter connects traditionally distinct "siloed" functional expertise and provides listeners with practical knowledge and tools to help them understand the entire M&A process; from pre-deal strategy and due diligence, through transaction valuation, negotiations, and consummation, to post-deal implementation, workforce motivation, innovation for revenue growth, and results measurement and reporting. Case examples illustrate how each stage of the process has been implemented by companies across various industries.Through an actionable, end-to-end process model this book shows both practitioners and students of M&A how to successfully mobilize and integrate organizational capability and avoid management missteps to gain a unique advantage and truly "win" at the acquisition game.